Intestinal permeability in patients with chemotherapy-induced stomatitis - Melichar, B; Kohout, P; Brátová, M; Solichová, D; Králícková, P; Zadák, Z (Journal of cancer research and clinical oncology, 2001)
PURPOSE: Mucositis represents one of the most common side effects of chemotherapy, and may affect any part of the gastrointestinal tract, resulting in stomatitis, dysphagia, dyspepsia, or diarrhea. The aim of the present study was to evaluate intestinal permeability in patients with stomatitis during treatment with oral granulocyte-monocyte colony-stimulating factor (GM-CSF, Leucomax). METHODS: Ten patients with chemotherapy-induced stomatitis and 21 control cancer patients were included in the study. Intestinal permeability in patients with stomatitis was evaluated before and after the treatment with oral GM-CSF (200 micrograms for 4 consecutive days) by measuring urinary lactulose, D-xylose, and mannitol after oral challenge in collected urine using capillary gas chromatography. RESULTS: Mean grade of stomatitis (3, range 2-3) improved during treatment by a mean of 1 grade (range 0-2, sign test P < 0.05) with an improvement observed in eight of ten patients. Lactulose excretion, lactulose/mannitol, and lactulose/xylose ratios were markedly elevated in the patients with mucositis compared with 21 control cancer patients (1.60 +/- 1.04%, 0.2446 +/- 0.2937, and 0.3877 +/- 0.6808 vs 0.35 +/- 0.20%, 0.0332 +/- 0.0148, and 0.0255 +/- 0.0086, respectively, Mann Whitney U-test, P < 0.001). After treatment, lactulose excretion, lactulose/mannitol, and lactulose/xylose ratio decreased significantly (1.60 +/- 1.04 vs 0.63 +/- 0.42%; 0.2446 +/- 0.2937 vs 0.1303 +/- 0.1149; and 0.3877 +/- 0.6808 vs 0.1126 +/- 0.1146, respectively, P < 0.05). CONCLUSIONS: Lactulose excretion after oral challenge, lactulose/mannitol, or lactulose/xylose ratio may be useful markers for intestinal involvement in chemotherapy-induced mucositis. Improvement of oral mucositis was associated with a significant decrease of intestinal permeability to lactulose. Testing of intestinal permeability by the present method may be useful to evaluate the effect of therapeutic interventions in patients with chemotherapy-induced mucositis.
Keywords: Stomatitis; výsledek terapie; doxorubicin; mannitol; permeabilita; Male; ftorafur; laktulosa; deoxycytidin; Antineoplastic Combined Chemotherapy Protocols; hodnocení léčiv; Gemcitabine; Mannitol; faktor stimulující granulocyto-makrofágové kolonie; Fluorouracil; střevní sliznice; leukovorin; intestinální absorpce; mužské pohlaví; paclitaxel; Paclitaxel; Tegafur; Permeability; Treatment Outcome; lidé; fluoruracil; ženské pohlaví; Digestive System Neoplasms; Leucovorin; xylosa; Humans; nádory trávicího systému; Intestinal Mucosa; stomatitida; protokoly protinádorové kombinované chemoterapie; Lactulose; Intestinal Absorption; Granulocyte-Macrophage Colony-Stimulating Factor; cisplatina; Drug Evaluation; Female; Cisplatin; Xylose; lidé středního věku; gemcitabin; Doxorubicin; Middle Aged; Deoxycytidine